2013
DOI: 10.36880/c04.00695
|View full text |Cite
|
Sign up to set email alerts
|

Trade Openness, Financial Development, and Economic Growth in Turkey: Linear and Nonlinear Causality Analysis

Abstract: This paper aims at empirically investigating the direction of causality among trade liberalization, financial development, and economic growth in Turkey. By employing monthly data for the period January, 1989- November, 2007, both linear and nonlinear causality approaches indicate that (i) there is bi-directional causality between economic growth and trade openness, (ii) economic growth causes financial development, and (iii) financial development leads to trade liberalization. Thereby, linear and nonlinear ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 43 publications
5
28
0
9
Order By: Relevance
“…This study suggests a positive and significant impact of financial development and economic growth. Our outcome is parallel with numerous prior investigations (Ahmed & Hasnu, 2009;Guo et al, 2008;Kar & Pentecost, 2000). This finding disapproves the arguments of researchers such as Brownbridge & Kirkpatrick, (2000); De Gregorio & Guidotti, (1995); Demirgüç -Kunt & Detragiache, (1998,2000); Gourinchas, Valdes, & Landerretche, (2001); Kaminsky & Reinhart, (1999);Schneider & Tornell, (2004) among others who are of the view that financial development may hinder economic growth.…”
Section: Discussion and Analysissupporting
confidence: 83%
“…This study suggests a positive and significant impact of financial development and economic growth. Our outcome is parallel with numerous prior investigations (Ahmed & Hasnu, 2009;Guo et al, 2008;Kar & Pentecost, 2000). This finding disapproves the arguments of researchers such as Brownbridge & Kirkpatrick, (2000); De Gregorio & Guidotti, (1995); Demirgüç -Kunt & Detragiache, (1998,2000); Gourinchas, Valdes, & Landerretche, (2001); Kaminsky & Reinhart, (1999);Schneider & Tornell, (2004) among others who are of the view that financial development may hinder economic growth.…”
Section: Discussion and Analysissupporting
confidence: 83%
“…Whereas a,b,c,d are constant terms and j 1 2 Shahbaz et al (2008), Marques et al (2013) and Kar and Pentecost (2000) also applied…”
Section: Methodsmentioning
confidence: 99%
“…Some, in addition, found significant evidence that economic growth will create demand for the various financial services that the financial system will provide. Supporters of demand leading hypothesis were Robinson (1952), Kar and Pentecost (2000), Ansari (2002), Favara (2006), Kandir et. al.…”
Section: Literaturementioning
confidence: 96%
“…Almost all micro studies on the effects of bank credits in Turkey can be observed to have used GDP as dependent variable (Kar and Pentecost, 2000;Aslan and Kucukaksoy, 2006;Onder and Ozyıldırım, 2010;Kaya et al, 2013;Bayar and Tokpunar, 2014). It is clear that GDP is a very general concept and is under the influence of all other sectors.…”
Section: Model Specification and Data Estimation Proceduresmentioning
confidence: 99%